Exploring the landscape of entrepreneurship in Pakistan: a comparative analysis of perceptions, challenges, and the need for psychoeducational interventions in the academic sector - Mehboob, Khurram; Ali, Muhammad; Hassan, Noor; Mehboob, Zeeshan; Mushtaq, Muhammad Faisal; Ullah, Rana Hamad; Zahid Akhtar, Muhammad; Tariq, Muhammad Akram; Parveen, Khalida; Mehboob, Riffat (Frontiers in Education, 2025)
ObjectivesEntrepreneurship in Pakistan is steadily growing, significantly impacting on economic development and job creation, despite facing several challenges. This study aimed to investigate the perceptions of students and faculty members about entrepreneurship in public and private universities in Pakistan. It also sought to evaluate the barriers and motivational factors promoting entrepreneurship among these universities.MethodsA cross-sectional study was conducted, and a comprehensive questionnaire was utilized to collect data. A total of 213 individuals from different disciplines took part in the study. This study examines the similarities and differences in the views of faculty members and students toward entrepreneurship by using SPSS 25.ResultsIn terms of motivation, 72% of private sector participants cited income satisfaction as a key factor, compared to 58% in the public sector. The proportion of participants willing to apply for funding for entrepreneurial support was 68%, predominantly among private sector participants (75% vs. 61%). Access to training programs was reported by 62%, but private universities provided 35% more institutional support. The results of the chi-squared test revealed that institutional business courses, startup funding, and funding applications were significantly correlated in public and private sectors. Key risks identified included a lack of access to funding (42%), inadequate workforce skills (37%), and limited market opportunities (29%). Fresh graduate entrepreneurial failures were attributed to lack of experience (43%) and market adaptability (33%). The study also highlighted the connection between entrepreneurial activities and mental health issues, including frustration, burnout, and a lack of motivation for business. Both groups showed similar perceptions regarding business potential and suggested mentorship as a key area for improving entrepreneurship.ConclusionThe study suggests that promoting entrepreneurship in Pakistan should focus on targeted interventions through the initiation of psychoeducational training, networking opportunities, and mentorship. Additionally, these policies should identify the sectoral issues they aim to solve while incorporating mental health policies to create a robust entrepreneurial ecosystem. Extending the study to include various industries and stakeholders will be another direction for future research to improve policy and practice.